2016
DOI: 10.1016/j.phrs.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

The novel mitochondria-targeted hydrogen sulfide (H 2 S) donors AP123 and AP39 protect against hyperglycemic injury in microvascular endothelial cells in vitro

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 65 publications
3
101
1
1
Order By: Relevance
“…Hyperglycaemia leads to mitochondrial superoxide generation, which initiates endothelial dysfunction and oxidant production [32]. H 2 S serves as an electron donor to the respiratory chain and plays a therapeutic role in DM and vascular diseases [33, 34]. A recent in vitro study also showed that H 2 S inhibits Aβ-induced neuronal apoptosis by regulating mitochondrial function [35].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycaemia leads to mitochondrial superoxide generation, which initiates endothelial dysfunction and oxidant production [32]. H 2 S serves as an electron donor to the respiratory chain and plays a therapeutic role in DM and vascular diseases [33, 34]. A recent in vitro study also showed that H 2 S inhibits Aβ-induced neuronal apoptosis by regulating mitochondrial function [35].…”
Section: Introductionmentioning
confidence: 99%
“…At later stages, changes in the expression or assembly of some components of the respiratory chain may occur and these are typically associated with impaired functionality [98,99]. The glucose-induced changes in the mitochondrial superoxide production are reversible: normalization of the membrane potential suppresses the ROS production in endothelial cells [26,35,83,94,100]. While elevated mitochondrial membrane potential is detectable in endothelial cells exposed to high glucose concentration, the overexpression of either uncoupling protein 1 (UCP1) or uncoupling protein 2 (UCP2) normalizes the membrane potential and reduces the ROS production [26,35,83].…”
Section: The Mechanism Of Glucose-induced Mitochondrial Superoxide Gementioning
confidence: 99%
“…The function of UCP2 is regulated by ROS itself: the proton conductance of the protein is controlled by glutathionylation, and if ROS is present, it increases the proton leakage, whereas in the absence of ROS, the channel closes, thus this feedback may control the mitochondrial potential and the ROS production simultaneously [32,33]. Furthermore, hydrogen sulfide donors that normalize the mitochondrial potential by electron supplementation via sulfide:quinone oxidoreductase (SQR) also inhibit the superoxide generation induced by hyperglycemia [94,100].…”
Section: The Mechanism Of Glucose-induced Mitochondrial Superoxide Gementioning
confidence: 99%
“…Hyperglycemia is characteristic of type 2 diabetes and the metabolic syndrome, where high levels of glucose in the blood lead to intracellular oxidative stress, especially in tissues involved in glucose metabolism [1][2][3]. Although mitochondria are a source of oxidative stress, they are also a principal target of attack by reactive oxygen and nitrogen species [4,5] and, once above certain thresholds, insulin sensitivity and secretion are hampered [6,7].…”
Section: Introductionmentioning
confidence: 99%